PANDANGAN ULAMA TENTANG JILBAB: TREND GAYA BUSANA DAN PERILAKU KEAGAMAAN SANTRI - Iis Islahudin (QATHRUNÂ, 2019)
The purpose of this study is to explain the limits of the genitals of Muslim women and the headscarf from various perspectives of the views of the scholars, which are studied in multiple interpretations. Understanding the Muslim hijab is one of the knowledge that can be owned by every individual and is one of the knowledge that is considered important. By having an understanding of the veil and genitals, it is hoped that santriwati will be able to behave religiously in accordance with the Shari'a and their fashion styles in accordance with the rules determined by Islamic law. The research method used in this research study is a qualitative approach. The number of research respondents was 20 santriwati. The research location is in the Raudhatul Jannah Malingping Islamic Boarding School. Data collection used is through interviews, observation, and documentation study. Data analysis used is through triangulation of data which is then converted into a conclusion in the form of a proposition as the final form of qualitative study. The results of this study are that the scholars have different opinions about the limits of Muslim genitalia which have implications for the use of the hijab, the majority of scholars say that the hijab is mandatory with the boundaries of the face and palms visible, some scholars say that the face and palms are included in the genitals. . A small number of scholars say that the use of the headscarf is not mandatory, therefore the exposed hair, hands and feet can be seen because it is not part of the genitals for women. 1) the opinions of the scholars who oblige the veil are Ibn Abbas, Sayyid Qutb, Ibn Katsir, Wahbah Az-Zuhaili, and Yusuf Qaradhawi, 2) The opinions of scholars who do not require the hijab are Quraish Syihab, Nurkholis Madjid, Muhammad Sa'id Al-Asmawi, and Muhammad Shahrur.